English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

when i solve it i get
3x^2+ 3x - 2x - 2 = 0
3x^2 +x - 2 = 0

but its the next part that i get confussed at
Please explain to answer to me

2007-01-14 07:59:21 · 7 answers · asked by Anonymous in Science & Mathematics Mathematics

7 answers

3x^2+3x-2x-2=0
(3x^2+3x)+(-2x-2)=0
3x(x+1)-2(x+1)=0
(3x-2)(x+1)=0
x= 2/3 or -1

2007-01-14 08:04:14 · answer #1 · answered by      7 · 0 0

i visit apply a diverse difficulty, notwithstanding the same significant. x(squared)+5x+6=0 you want to discover what multiples of the first quantity (6) will upload as a lot because the second one quantity (5) so enable's see: 1x6= 6, yet a million+6=7. 2x3=6, and a couple of+3=5! 2 and three are your multipliers! Now, you should undergo in ideas the positives and negatives interior the precedence. on your difficulty, you want a assorted of -a million which will upload as a lot as -2. next you're making little parenthesis containers like this: ( ) ( ) = 0 and fill them in with the fantastic assorted: ( +2) ( +3) = 0 Now you upload the x (x+2)(x+3) = 0 Now the kind of has to equivalent 0, because something elevated by technique of 0 equals 0. so that you've 2 recommendations, both x+2=0, or x+3+0. this suggests, (from undemanding simplification) x = -2 or -3 and there is your answer. Does that make any experience in any respect? If that would not artwork, use the quadratic formulation that L gave you.

2016-11-23 18:14:00 · answer #2 · answered by crossland 4 · 0 0

WHen i was in algebra two, my teacher taught this to me. IF you multiply the first and last coefficients (three and -two) you get -six. Now you see which multiples of -six add to one. -one and six? no one and -six? no -three and two? no -two and three? YES. so you lay it out like this: 3x^2 + 3x -2x - 2=0 (always put the inside numbers in a spot next to the outside one that it best divides into: You wouldn't do 3x^2-2x+3x-2) Then you can take out the common number so you get 3x(x+1)-2(x+1)=0 (which happens to be the original equation, but you can't always count on that being the case). Then since they both have x+1 in common you can do the following (x+1)(3x-2)=0 and x= -one or two-thirds. (You just take the front of the parentheses). If you don't get it (cause it is kind of hard to explain without being facetoface, contact me and I'll try explaining differently). Sorry for the messy explaination. I hope it helps anyway:D

2007-01-14 08:16:00 · answer #3 · answered by InlovewithTalon 2 · 0 0

3x(x+1)-2(x+1)=0

3x^2 + 3x - 2x - 2 = 0

3x^2 + x - 2 = 0

(3x - 2)(x + 1) = 0

therefore:

3x - 2 = 0
x = 2/3

x + 1 = 0
x = -1

solutions: -1, 2/3

2007-01-14 08:05:57 · answer #4 · answered by Anonymous · 0 0

From where you left off..

(3x - 2)*(x + 1) =

So x = 2/3 or x = -1

2007-01-14 08:02:18 · answer #5 · answered by JasonM 7 · 1 0

the answer is 3 x 2(3 x square)+ x - 2
the work i did was 3 x 2 +3 x - 2 x - 2= but the answer was the first thing i wrote hope i helped!

2007-01-14 08:09:51 · answer #6 · answered by princess 1 · 0 0

3x²+x-2=(3x-2)(x+1)

(3x-2)(x+1)=0
x=-1 or 2/3

2007-01-14 08:03:27 · answer #7 · answered by A 150 Days Of Flood 4 · 0 0

fedest.com, questions and answers